Chitosan-based biomaterial delivery strategies for hepatocellular carcinoma - Wang, Xianling; Yang, Yan; Zhao, Shuang; Wu, Di; Li, Le; Zhao, Zhifeng (Frontiers in Pharmacology, 2024)
Background: Hepatocellular carcinoma accounts for 80% of primary liver cancers, is the most common primary liver malignancy. Hepatocellular carcinoma is the third leading cause of tumorrelated deaths worldwide, with a 5-year survival rate of approximately 18%. Chemotherapy, although commonly used for hepatocellular carcinoma treatment, is limited by systemic toxicity and drug resistance. Improving targeted delivery of chemotherapy drugs to tumor cells without causing systemic side effects is a current research focus. Chitosan, a biopolymer derived from chitin, possesses good biocompatibility and biodegradability, making it suitable for drug delivery. Enhanced chitosan formulations retain the anti-tumor properties while improving stability. Chitosan-based biomaterials promote hepatocellular carcinoma apoptosis, exhibit antioxidant and anti-inflammatory effects, inhibit tumor angiogenesis, and improve extracellular matrix remodeling for enhanced antitumor therapy. Methods: We summarized published experimental papers by querying them.Results and Conclusions: This review discusses the physicochemical properties of chitosan, its application in hepatocellular carcinoma treatment, and the challenges faced by chitosan-based biomaterials.